ECONOMIC LITERACY, LIFESTYLE AND SELF-CONTROL OF STUDENT CONSUMPTIVE BEHAVIOR FACULTY OF ECONOMICS, JAKARTA STATE UNIVERSITY - Indriyani, Vivia Aegea; Mukhtar, Saparuddin; Wiralaga, Harya Kuncara (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the effect of economic literacy, lifestyle, and self-control on the consumptive behavior of students at the Faculty of Economics, Jakarta State University. The method used in this study is a quantitative method. The reachable population in this study were all undergraduate students at the Faculty of Economics, Jakarta State University for the 2021/2022 academic year with a total of 97 students. Sampling technique with simple random sampling, with data collection using questionnaires and tests. The analysis technique used in this research is path analysis. The results of this study indicate that: 1) Economic Literacy has a negative and significant effect of -62.7% on Consumptive Behavior, 2) Lifestyle has a positive and significant effect of 76.6% on Consumptive Behavior, 3) Self-control has a negative effect of - 43.5% on Consumptive Behavior, 4) Economic Literacy, Lifestyle and Selfcontrol together have a positive and significant effect of 79.3% and the rest are influenced by other factors.